Gender policy in Ukraine: features of legislative practice - Vadym Novak; Yuliia Maslova; Walery Zukow (Nicolaus Copernicus University in Toruń, Poland - University Sports Center, 2020)
The article analyses the main legislative and theoretical initiatives of Ukraine, as a state unit, regarding the implementation of gender policy, observance and realization of equal rights and opportunities of men and women in all spheres of public life of the state.